Analisis Kebangkrutan pada Perusahaan Food dan Bevarage yang Terdaftar di Bursa Efek Indonesia - Nety Torano (Departement of Mathematics Education, 2023)
Financial ratio analysis is an analytical technique to help evaluate a company's financial statements by combining the numbers in or between profit and loss and balance sheet. Financial ratios are useful for identifying a company's financial strengths and weaknesses. The Altman Z-Score is expressed in the form of a linear equation consisting of 5 X coefficients representing certain financial ratios. While the formula is as follows (Altman, 1968), Z = 1.2X1 + 1.4X2 + 3.3X3 + 0.6X4 + 0.999X5. Based on the results of the Z-Score analysis and discussion, it shows that all of the four food and beverage companies listed on the Indonesia Stock Exchange have fluctuated, meaning that there is a tendency to be in a state of bankruptcy, a gray area or in a non-bankrupt state. From the calculation of the Z-Score prediction, there is only one company, namely PT Mayora Indah, Tbk which can maintain the company's health condition. Meanwhile, PT Akasha Wira International, Tbk, then PT Indofood Sukses Makmur, Tbk and PT Ultra Jaya Milk, Tbk are in a vulnerable zone, namely entering the gray area and even the bankrupt area. PT Indofood Sukses Makmur, Tbk is a company that has a tendency to be in an unsafe zone because it is classified as bankrupt, meaning that the company is experiencing financial difficulties which have an impact on the continuity of the company.